Implementation of the Multicultural Islamic Religious Education Curriculum in Madrasa - Muhammad Yusuf; Sri Wahyuni (Journal of Contemporary Islamic Education, 2025)
Indonesia is a country with rich cultural, religious, and ethnic diversity, and education plays a central role in forming attitudes and behaviors that are tolerant and respect differences. However, the existing Islamic Religious Education (IRE) curriculum is often unable to accommodate the needs of inclusive and multicultural education, tending to focus on doctrinal aspects. This research aims to identify and analyze the implementation of multicultural IRE curriculum development strategies at Darut Taqwa Favorite Madrasah Tsanawiyah (MTs). This research uses a qualitative approach with field research and literature study methods to collect data from in-depth interviews, observation, and documentation. The research results show that MTs Favorit Darut Taqwa has integrated multicultural values ​​into the IRE curriculum through strategies such as thematic learning, case studies, and extracurricular activities. Challenges faced include limited resources and limited time in the lesson schedule. The proposed strategy includes strengthening teacher training, developing teaching materials, collaborating with the community, and ongoing evaluation and monitoring. The implementation of the multicultural IRE curriculum at MTs Favorit Darut Taqwa has had a positive impact on students' attitudes and social skills, forming a tolerant and inclusive generation and contributing to strengthening multicultural education in Indonesia.